Skin and Soft Tissue Infections in Patients with Solid Tumours - Diamantis P. Kofteridis; Antonios Valachis; Eirini Koutsounaki; Sofia Maraki; Eleni Mavrogeni; Foteini N. Economidou; Dimitra Dimopoulou; Kostas Kalbakis; Vassilis Georgoulias; George Samonis (The Scientific World Journal)
Background. Skin and soft tissue infections (SSTIs) in cancer patients represent a diagnostic challenge, as etiologic diagnosis is often missing, and clinical assessment of severity is difficult. Few studies have described (SSTIs) in patients with solid tumours (STs). Patients and Methods. Records of patients with ST and SSTI, cared for at the University Hospital of Heraklion, from 2002 to 2006 were retrospectively studied. Results. A total of 81 episodes of SSTIs, occurring in 71 patients with ST, have been evaluated. Their median age was 65 years (34–82). The most common underlying malignancy was breast cancer in 17 patients (24%). Most episodes (89%) occurred in nonneutropenics. Cellulitis/erysipelas was the most common clinical presentation (56; 69%). Bacterial cultures were possible in 29 (36%) patients. All patients received antimicrobial therapy, while in 17 episodes (21%) an incision and drainage was required. Treatment failure occurred in 20 episodes (25%). Five patients (7%) died due to sepsis. None was neutropenic. Severe sepsis on admission (𝑃=0.002) and prior blood transfusion (𝑃=0.043) were independent predictors of treatment failure. Conclusion. SSTIs can be life threatening among patients with ST. Early diagnosis and appropriate treatment are of the utmost importance, since sepsis was proven a significant factor of unfavourable outcome.